Changes in ischemia-modified albumin in myocardial toxicity induced by anthracycline and docetaxel chemotherapy. Issue 32 (August 2017) - Luan, Xiao-Dong; Zhao, Kai-Hua; Hou, Hong; Gai, Yan-Hong; Wang, Qi-Tang; Mu, Qiang; Wan, Yue
Abstract : Abstract: This study aims to evaluate differences in myocardial toxicity induced by different chemotherapy regimens. Patients were divided into 2 groups: epirubicin (EPI) combined with cyclophosphamide (EC) group and docetaxel combined with cyclophosphamide (TC) group. Changes in electrocardiograph (ECG) and ischemia-modified albumin (IMA) were determined pre- and 1, 3, and 6 courses of postchemotherapy. After the first course of chemotherapy, there was no significant difference in ECG and abnormal IMA incidence rates between the TC groups and EC groups ( P  > .05). After the third course and at the end of the sixth course, ECG and abnormal IMA incidence rates in the EC group were significantly higher than in the TC group ( P  < .05). Besides, IMA values significantly increased with the increase in chemotherapy courses in the EC group; and the value of the postsixth course was significantly higher than in the pre- and postfirst and -third courses of chemotherapy. IMA value in the postsixth course in the TC group was significantly higher than that in the pre- and postfirst and -third courses of chemotherapy. In addition, IMA values at the postfirst and -third courses of chemotherapy in the EC group were significantly higher than in the TC group. Both EC and TC chemotherapy regimens were harmful to the myocardium, and the incidence rate of myocardial damage increased with the increase of cumulative dose. Besides, the degree of myocardial damage in EC group was significantly higher than in the TC group.